Interplay between unconventional superconductivity and heavy-fermion quantum criticality: CeCu2Si2 versus YbRh2Si2. Issue 32 (12th November 2018) - Smidman, M.; Stockert, O.; Arndt, J.; Pang, G. M.; Jiao, L.; Yuan, H. Q.; Vieyra, H. A.; Kitagawa, S.; Ishida, K.; Fujiwara, K.; Kobayashi, T. C.; Schuberth, E.; et al.
ABSTRACT: In this paper the low-temperature properties of two isostructural canonical heavy-fermion compounds are contrasted with regards to the interplay between antiferromagnetic (AF) quantum criticality and superconductivity. For CeCu2 Si2, fully-gapped d -wave superconductivity forms in the vicinity of an itinerant three-dimensional heavy-fermion spin-density-wave (SDW) quantum critical point (QCP). Inelastic neutron scattering results highlight that both quantum critical SDW fluctuations as well as Mott-type fluctuations of local magnetic moments contribute to the formation of Cooper pairs in CeCu2 Si2 . In YbRh2 Si2, superconductivity appears to be suppressed at T  ⪆ 10 mK by AF order ( T N  = 70 mK). Ultra-low temperature measurements reveal a hybrid order between nuclear and 4 f -electronic spins, which is dominated by the Yb-derived nuclear spins, to develop at T A slightly above 2 mK. The hybrid order turns out to strongly compete with the primary 4 f -electronic order and to push the material towards its QCP. Apparently, this paves the way for heavy-fermion superconductivity to form at T c  = 2 mK. Like the pressure – induced QCP in CeRhIn5, the magnetic field – induced one in YbRh2 Si2 is of the local Kondo-destroying variety which corresponds to a Mott-type transition at zero temperature. Therefore, these materials form the link between the large family of about fifty low- T unconventional heavy – fermion superconductors and other families of unconventional superconductors with higher T c s, notably the doped Mott insulators of the cuprates, organic charge-transfer salts and some of the Fe-based superconductors. Our study suggests that heavy-fermion superconductivity near an AF QCP is a robust phenomenon.